Proximate composition and fatty acid profile of palm weevil (rhynchophorus spp.) larvae, herbivores of sago (Metroxlon sagu Rottb.) - Bernardino, Melissa D. (2005)
The larvae of palm weevils (Rhynchophorus spp.) form an important food source for the locals of Agusan del Sur, thus, the proximate composition and fatty acid profile of raw palm weevil lavae were determined. Sixty-five live Rhynchophorus spp. Larvae were collected from palm weevil-infested sago palms in selected areas in Agusan del Sur. Samples were divided into three sample lots according to size, decapitated and homogenized prior to proximate analysis. Crude oil was extracted using the solvent extraction Soxtec system and the Rhynchophorus spp. Larvae oil from sample lot C was analyzed through gas chromatography to determine its fatty acid composition. Proximate composition analysis showed that sizes of Rhynchophorus spp. Larvae that are commonly eaten, which are from sample of lot C, have mean values of 56.16% moinsture, 1.88% ash, 65.50% fat, 14.37% fiber, 14.48% protein and 3.77% nitrogen-free extract, dry basis. Significant difference (P<0.05) was observed in the moisture, ash, crude fat, crude fiber, crude protein and nitrogen-free extract contents among the three lots. Results of the fatty acid profile of the larvae oil showed to contain 1.17% myristic (C14:0), 40.38% palmitic (C16:0), 2.53% stearic (C18:0), 48.59% oleic (C18:1) and 1.34% linoleic (C18:2) acids and 5.99% unknown. Unsaturation content is 40.93%, with oleic acid being the dominant fatty acid in the lipid content. High percentage of oleic acid found in Rhynchophorus larvae oil is indicative of its high nutritive value